Joint association of systemic immune-inflammation index and phenotypic age acceleration with chronic respiratory disease: a cross-sectional study - Yuan Zhan; Ruonan Yang; Jie Feng; Genlong Bai; Xiangyun Shi; Jiaheng Zhang; Jingbo Zhang (BMC Public Health)
Abstract Background Chronic respiratory diseases (CRD) represents a series of lung disorders and is posing a global health burden. Systemic inflammation and phenotypic ageing have been respectively reported to associate with certain CRD. However, little is known about the co-exposures and mutual associations of inflammation and ageing with CRD. Here, we aim to systematically elucidate the joint and mutual mediating associations of systemic immune-inflammation index (SII) and phenotypic age acceleration (PhenoAgeAccel) with CRD based on data from National Health and Nutrition Examination Survey (NHANES). Methods Data for this study was obtained from NHANES 2007–2010 and 2015–2018. The single and combined associations of SII and PhenoAgeAccel with CRD were analyzed using multivariable logistic regression models. The dose-response relationship between exposures and outcomes was determined by restricted cubic splines (RCS) regression. Subgroup and mediation analyses were further conducted. Results Totally, 15,075 participants were enrolled in this study including 3,587 CRD patients. Compare with controls, CRD patients tended to be older, females and present higher SII and PhenoAgeAccel values. Single-index analysis indicated that either SII or PhenoAgeAccel demonstrated a significantly positive association with CRD via logistic regressions and RCS curves. Furthermore, the joint-indexes analysis revealed that compared to individuals with lower SII and PhenoAgeAccel, those with higher SII and PhenoAgeAccel exhibited remarkably stronger associations with CRD (adjusted OR [aOR], 1.56; 95% CI, 1.31–1.85; P < 0.001), chronic obstructive pulmonary disease (aOR, 1.56; 95% CI, 1.22-2.00; P = 0.001) and asthma (aOR, 1.40; 95% CI, 1.16–1.70; P = 0.001), which were predominant among those aged above 40 years, females and smokers. Eventually, mediation analyses suggested the mutual mediating effects of SII and PhenoAgeAccel on CRD and PhenoAgeAccel mediated SII resulting in CRD more significantly. Conclusion This study confirmed the coexposure effect and mutual mediation between SII and PhenoAgeAccel on CRD. We recommend that the joint assessment may conduce to the accurate identification for populations susceptible to CRD and early prevention of chronic respiratory diseases.